Historical education in Portugal: learning goals in the early years of schooling - Isabel Barca; Gloria Solé (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The Learning Outcomes Project for K-Basic Schooling recently carried out in Portugal intended to produce a set of learning outcomes for each curriculum subject matter or area. It has aimed to provide a set of useful tools to the teaching process, thus promoting student achievement. With respect to the History Learning Outcomes, their team got inspiration in relevant empirical studies on situated historical cognition grounded on recent epistemological perspectives concerning history. Under this framework, this paper discusses some of the “History Learning Outcomes” for K-Cycle 1 (3-10 year-olders), seen as significant in the light of historical thinking and consciousness.